Population Pharmacokinetics of Indinavir in Patients Infected with Human Immunodeficiency Virus - Csajka, Chantal (American Society for Microbiology, 2004)
Indinavir is currently used at a fixed dose of 800 mg either three times a day or twice a day in combination with 100 mg of ritonavir. Dosage individualization based on plasma concentration monitoring might, however, be indicated. This study aimed to assess the pharmacokinetic profile of indinavir in patients infected with human immunodeficiency virus to characterize interpatient and intrapatient variability and to build up a Bayesian approach for dosage adaptation. A population analysis was performed with the NONMEM computer program with 569 plasma samples from a cohort of 239 unselected patients receiving indinavir. A one-compartment model with first-order absorption was adapted, and the influences of clinical characteristics on oral clearance (CL) and distribution volume (V) were examined. Predicted average drug exposure and trough and peak concentrations were derived for each patient and correlated with efficacy and toxicity markers. The population estimates of CL were 32.4 liters/h for female and 42.0 liters/h for male patients; oral V was 65.7 liters; and the rate constant of absorption (K(a)) was 1.0 h(−1). CL decreased by 63% with ritonavir intake and was moderately correlated to body weight. Both interpatient variability, best assigned to oral CL (coefficient of variation [CV], 39%) and K(a) (CV, 67%), and intrapatient variability were large (CV, 41%; standard deviation, 670 μg/liter). In conclusion, initial indinavir dosage should be decided according to ritonavir intake and sex, prior to plasma concentration measurements. The high interpatient pharmacokinetic variability represents an argument for therapeutic drug monitoring.